Application of the Filariasis CELISA Antifilarial IgG4 Antibody Assay in Surveillance in Lymphatic Filariasis Elimination Programmes in the South Pacific. (26th September 2011) - Joseph, Hayley; Maiava, Fuatai; Naseri, Take; Taleo, Fasihah; 'Ake, Malakai; Capuano, Corinne; Melrose, Wayne
Abstract : Elimination of lymphatic filariasis (LF) in the Pacific Island Countries and Territories (PICT) has been defined as <0.1% circulating filarial antigen (CFA) prevalence in children born after the implementation of successful mass drug administrations (MDAs). This research assessed the feasibility of CFA and antibody testing in three countries; Tonga, Vanuatu, and Samoa. Transmission is interrupted in Vanuatu and Tonga as evidenced by no CFA positive children and a low antibody prevalence and titre. Transmission is ongoing in Samoa with microfilaraemic (Mf) and CFA positive children and a high antibody prevalence and titre. Furthermore, areas of transmission were identified with Mf positive adults, but no CFA positive children. These areas had a high antibody prevalence in children. In conclusion, CFA testing in children alone was not useful for identifying areas of residual endemicity in Samoa. Thus, it would be beneficial to include antibody serology in the PICT surveillance strategy.